Behavioral, physiological and morphological correlates of parasite intensity in the wild Cururu toad (Rhinella icterica) - Moretti, Eduardo Hermogenes [UNESP]; Titon, Braz [UNESP]; Madelaire, Carla Bonetti [UNESP]; Arruda, Raquel de [UNESP]; Alvarez, Tatiana [UNESP]; Gomes, Fernando Ribeiro [UNESP] (Elsevier B.V., 2017)
Large numbers of parasites are found in various organs of anuran amphibians, with parasite intensities thought to modulate the host's Darwinian fitness traits. Interaction between the anuran hosts and their multiple parasites should modulate the host's phenotypic characteristic, such as those associated with high energetic demand (such as calling effort and locomotor performance), energy balance (standard metabolic rate), and morphological plasticity (as indicated by organ masses). The present study investigated the impact of parasite intensities on the behavioral, physiological, and morphological traits of wild adult male Rhinella icterica (Anura: Bufonidae). We tested as to whether individuals with higher parasite intensities would present: 1) lower vocal calling effort in the field, as well as poorer locomotor performance and body-condition index; and 2) higher standard metabolic rates and internal organ masses. Measurements included: calling effort in the field; standard metabolic rate; locomotor performance; parasite intensity; internal organ masses (heart, liver, kidneys, intestines, stomach, lungs, hind limb muscle, and spleen); and the body-condition index. Results showed a negative association of parasite intensities with locomotor performance, and standard metabolic rate of R. icterica. A positive association between parasite intensities and relative organ masses (heart, intestines and kidneys) was also evident. Toads with higher pulmonary and intestinal parasites intensities also showed higher total parasite intensities. (C) 2017 The Authors. Published by Elsevier Ltd on behalf of Australian Society for Parasitology.
Keywords: Bufonidae; Locomotor performance; Metabolic rate; Vocal effort; Rhabdias; Parasite association